Perceived neighborhood environment and physical activity among high school students from Curitiba, Brazil - Adalberto Aparecido dos Santos Lopes; Alessandra Nunes Lanzoni; Adriano Akira Ferreira Hino; Ciro Romélio Rodriguez-Añez; Rodrigo Siqueira Reis (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVE: To analyze the association between perceived neighborhood environment and physical activity (PA) in high school students from Curitiba (PR), Brazil. METHODS: A sample of 1,611 high school students from public schools was surveyed. The PA was assessed through questions, engaged for at least 20 minutes or 60 minutes. Perceptions on neighborhood environment were assessed through ten questions about neighborhood characteristics. Gender, age and number of cars in the household were self-reported and used as confounding variables. Absolute and relative frequencies were used in the sample, and associations were tested through adjusted logistic regressions for the confounding variables and stratified by gender (p < 0.05). RESULTS: The adjusted analyses showed that the variables "interesting things" among girls (OR = 1.77; 95%CI 1.05 - 2.96) and "there are places I like" (OR = 2.18; 95%CI 1.33 - 3.58) and "I see people my age", among boys, were associated with PA of at least 20 minutes/day once a week. Additionally, among boys, "I see people my age" was associated with 60-minute (OR = 1.68; 95%CI 1.15 - 2.45). Perceiving the neighborhood environment as "very good" was associated with higher chances of taking up PA among girls (OR = 1.92; 95%CI 1.15 - 3.22) and boys (OR = 3.13; 95%CI 1.97 - 4.97). CONCLUSION: A positive perception of the environment was associated to PA practice among boys and girls in this sample. The results suggest that some environmental characteristics which make neighborhoods more attractive could be related to PA among adolescents.